Development of new dermatological formulations for the treatment of cutaneous candidiasis. - Medegan Fagla, Sèdami R. (My University, 2020)
The inhibitory activity of the essential oils (EO) of mint and thyme on Candida albicans are well known, however, their valorization in a dosage form for the management of cutaneous candidiasis has been little explored. This study aimed to formulate innovative and cost-effective dermatological topicals based on mint and thyme essential oils for the treatment of cutaneous candidiasis. Thyme essential oil was obtained commercially, while that of mint was obtained by hydrodistillation. In order to determine their antifungal activity, both essentials oils were tested alone and in combination against a reference strain of Candida albicans (strain MHMR) and clinical strains of Candida albicans and Candida tropicalis. Three creams were formulated using natural (shea butter, palm oil) and chemical (cetomacrogol) excipients. The efficacies of these creams were assessed in vivo using Wistar rats infected with Candida albicans MHMR. The in vitro antimicrobial study showed that C. albicans MHMR was more sensitive to thyme essential oil with a MIC of 310 μgmL−1, which was higher than the reference fluconazole used for the in vitro study (32 μgmL−1). The antimicrobial synergy study of both essential oils using checkerboard test demonstrated an additive effect of mint and thyme essential oils on C. albicans MHMR. GC/FID and GC/MS analyses led to the identification of thymol and menthol respectively as the main components of thyme and mint essential oils. A shea butter cream base and a shea butter and palm oil cream both containing 5% of EO (mint and thyme) exhibited the best in vivo antimicrobial activities, inducing optimal wound healing in infected rats compared with ketoconazole commercial cream used for the in vivo study. These results provide a solid basis at least in part, for the use of essential oil in creams formulated with natural excipients for the management of cutaneous candidiasis.